THE USED OF VERBAL AND DEVERBAL NOUN IN MUNIBA MAZARI'S SPEECH - Rusita Dewi; Ida Ayu Putri Gita Ardiantari (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
This study entitled ‘The Use of Verbal and Deverbal Noun in Muniba Mazari’s Speech’ was conducted to find out the Verbal and Deverbal Nouns utilized in Muniba Mazari's speech. Nominalization in the form of verbal and deverbal nouns is critical while preparing a speech. Because the speaker must say anything with persuasive words in order to make a speech fascinating and readily persuade the audience, especially the subject and purpose of the speech. The speech was taken from written sources and videos on the internet. In this study, the qualitative descriptive approach is employed to clarify the data and research difficulties by applying the theory of nominalization by Quirk et al. A documentation approach was used to undertake the data collecting procedures. The documents utilized to support this study were videos and online transcriptions of the speech. The results revealed that there were 9 Verbal Noun data and 15 Deverbal Noun data from a total of 24 data.